Alternative Pathway Dysregulation and the Conundrum of Complement Activation by IgG4 Immune Complexes in Membranous Nephropathy - Borza, Dorin-Bogdan (Frontiers in Immunology, 2016)
Membranous nephropathy (MN), a major cause of nephrotic syndrome, is a non-inflammatory immune kidney disease mediated by IgG antibodies that form glomerular subepithelial immune complexes. In primary MN, auto-antibodies target proteins expressed on the podocyte surface, often phospholipase A2 receptor (PLA2R1). Pathology is driven by complement activation, leading to podocyte injury and proteinuria. This article overviews the mechanisms of complement activation and regulation in MN, addressing the paradox that anti-PLA2R1 and other antibodies causing primary MN are predominantly (but not exclusively) IgG4, an IgG subclass that does not fix complement. Besides immune complexes, alterations of the glomerular basement membrane (GBM) in MN may lead to impaired regulation of the alternative pathway. The alternative pathway amplifies complement activation on surfaces insufficiently protected by complement regulatory proteins. Whereas podocytes are protected by cell-bound regulators, the GBM must recruit plasma factor H, which inhibits the alternative pathway on host surfaces carrying certain polyanions, such as heparan sulfate chains. Because heparan sulfate chains present in the normal GBM are lost in MN, we posit that the local complement regulation by factor H may be impaired as a result. Thus, the loss of GBM heparan sulfate in MN creates a micro-environment that promotes local amplification of complement activation, which in turn may be initiated via the classical or lectin pathways by subsets of IgG in immune complexes. A detailed understanding of the mechanisms of complement activation and dysregulation in MN is important for designing more effective therapies.